TANGGUNG JAWAB NEGARA TERHADAP KEGAGALAN PERLINDUNGAN TERHADAP PEJABAT DIPLOMATIK ( STUDI KASUS PENEMBAKAN DUTA BESAR ITALIA UNTUK RD KONGO) - Elisabeth Septin Puspoayu; Afrizal Razqi; Ghina Maulida (Universitas Islam Syekh Yusuf, 2021)
The protection for diplomatic officials serving in the receiving country has been regulated in the 1961 Vienna Convention in all situations, the protection for diplomatic officials cannot be reduced. The shooting incident of the Italian Ambassador to the Democratic Republic of Congo while on duty in the territory of this country raises the obligation of accountability by the receiving country to the sending country. The rules for the protection of diplomatic officials and the inviolability of diplomatic officials according to diplomatic law, are under articles 29-30 and 41 of the Vienna Convention and Articles 33-36 of the 1961 Vienna Convention on Diplomatic Relations. protection includes the building, home, and self of the diplomatic officer on duty. Republic Democratic Congo as the recipient country must conduct an investigation and satisfaction with Italy. Keyword: diplomatic law; inviolability; and state responsibility.